DAYA TERIMA DAN PENGETAHUAN CALON PENGANTIN (CATIN) WANITA SEBELUM DAN SESUDAH EDUKASI GIZI MENGGUNAKAN APLIKASI 1000 HPK BERBASIS ANDROID - Erni; Rosmida Marbun; Fajar Meirani (Khazanah Intelektual, 2021)
The efforts to improve nutritional status for the human resources development must be started as early as possible, one of the things that can be done to improve nutrition status is the fulfillment of balanced nutrition in the period of 1000 first days of life (1000 HPK). This study aims to know the acceptability and the change of knowledge about 1000 HPK of brides at KUA Pesanggrahan District, South Jakarta by using the "My1000Days" application. The method that used in this study is Research and Development (R&D). There are 5 stages carried out in this study, namely: (1) needs analysis, (2) application product development, (3) feasibility testing by experts, (4) small-scale trials, (5) large-scale trials. The design used in this study was pre-experimental design with one group pre-post test design. The research samples were 40 brides. The results show that the acceptability of application by experts is 83% and the acceptability of application by brides is 95.7% which is categorized very well. Media feasible test get an n-gain value of 0.77 which is categorized as high and the results of the Paired t-test obtained a p value of 0.000 (p <0.5) which indicates knowledge difference before and after using the application. For this reason, it is necessary to further develop existing features to increase the knowledge regarding 1000 HPK of brides registered in KUA . Keywords: Android-based applications, Acceptability, 1000 HPK nutrition, Nutrition knowledge